Analisis Efektivitas dan Efisiensi Kinerja Pada Badan Amil Zakat Nasional Provinsi Kalimantan Selatan - Rizky Fadhillah; Irma Yulianti; Nurhidayati (P3M Politeknik Negeri Banjarmasin, 2024)
As an institution responsible for the management of zakat, BAZNAS must meet the criteria of strong, credible, efficient and effective. Efficiency and effectiveness are two indicators that can be used as benchmarks for a good management system in an institution. The results of measuring effectiveness and efficiency are expected to be able to improve the quality of zakat institutions, especially in terms of collection and distribution carried out by BAZNAS South Kalimantan Province. The method used is a quantitative descriptive method with primary and secondary data. The sample in this study is the financial report of BAZNAS South Kalimantan Province in 2019-2023. The research questions are about the level of effectiveness and efficiency of performance at BAZNAS South Kalimantan Province. The results showed that in the last 5 years the average effectiveness performance has been in the very effective category, there are only a few that show effective performance including Gross Allocation to Collections Ratio in 2020 and Gross Allocation to Collection Ratio Non-Mil in 2019 and on efficiency performance is in the inefficient category, only the collection ratio is in the effective category.